Turfas na planície costeira do Amapá: caracterização física , mineralógica e química - DELAVY, Francielli Paula Costa (2019)
The diversity of depositional environments gives to the Amapá Coastal Plain special conditions to the peat and peatlands formation. The physical, mineralogical and chemical characterization of this peat and peatlands is necessary due the absence of information about it ecological and economic potential, and justify itself due it widespread distribution, occurring at about 40% of the study area. The physical characteristics were done through the visual scale of van Post; the mineralogy through DRX while the chemical analysis were done by X-Ray fluorescence and through partial chemical extraction. The study area was divided in areas: Maracá, Macarry, Sucuriju, Tabaco e Linha Seca. The main results allow to differentiate at the coastal plain two different kinds of peat: fibrous with the main influence of fluvial and lacustrine environments as the ones found at the Tabaco and Linha Seca areas; e, hêmicas, the ones under the influence of coastal environments, as Maracá, Sucuriju e Macarry areas. The DRX analysis at the peat inorganic material has as primary minerals the quartz, muscovite, albite, feldspars and the goethite. The clay minerals were identified as the caulinite, chlorite and the smectite, while the neoformed minerals occurred as halite, pyrite and jarosite. The chemical composition of total peat ashes showed as main oxides the SiO2, Al2O3 , Fe2O3, SO3, with 63,88% of the total area followed by Na2O, MgO, CaO and K2O with 10,08% and minor amounts of MnO, P2O5 e TiO2. The functional groups identified practically in all analyzed samples and sre represented by bitumen, humic acid, carbohydrates and phenolic substances. The variations occurred at the intensity of the absorption bands according the ashes contents. The DTA analysis showed a first endothermic peak related to the material water losses. The range corresponding to the organic matter burns showed one or two endothermic peaks. The similarity between the identified mineralogy and mineralogical composition of recent sediments indicate that the peats can be used as an biological indicator of sedimentary processes and participate at the Quaternary geological evolution at the Amapá Coastal Plain.